(untitled) (Socio-Economic Development Panorama, 2008)
Nepal initiated steps to be associated with World Trade Organization (WTO) membership since thirteen years back. The challenges of becoming a full fledged member of WTO for a structurally fragile poor economic country like Nepal puts multifaceted challenges. It calls for revamping the overall development and educational strcutures of the nation. The article dwells on the current economic challenges of Nepal, namely concerned with poverty, unequal distribution of wealh, unbalanced development structure, and predominance of agriculture over trade and industrilization. Nepalese educational strucutre needs to be revamped, so as to cast the shadow of traditionalism, stagnation and multifaceted barriers. The stagnated mode of delivery which created obstacles needs to be diverted towards creation of an overall growth of the very nation State. It also underlines steps to take precautionary measures to utilize opportunities prevalent to emcompass WTO membership opportunities. This will help to provide legal dimension and bring forth a modern change in the work culture. It aims towards formulation of an acceleration of a growth oriented millenium goals strategy that the nation so aspires to achieve in the coming days ahead. Keywords: economy, education, world trade organization, WTO, prosperity, mode of delivery, international market, mode of supply Socio Economic Development Panorama, Vol. 1, No. 3(2008) pp. 131-146